The promises and pitfalls of global multi-stakeholder initiatives - Erik Lundsgaarde (Danish Institute for International Studies (DIIS), 2016)
Global multi-stakeholder initiatives seek to mobilize funding and expertise from diverse sources to address global development challenges. In an era of stagnant investment in bilateral and multilateral development cooperation, their aspiration to increase private sector support for the implementation of internationally-agreed goals is especially attractive. As this DIIS report highlights, factors such as the lack of fresh resources from public and private actors and inadequate attention to strategy development have limited multi-stakeholder initiatives from achieving their potential. In contrast, support for the development of secretariat functions, a clear definition of roles and responsibilities among participating stakeholders, and the identification of added value in a crowded landscape of cooperation initiatives can contribute to partnership success. This report presents findings from a study on the implementation of the Sustainable Energy for All (SE4ALL) initiative in Nepal to supplement existing assessments of global multi-stakeholder initiatives.
Keywords: 300